Thermoelectric Efficiency of Reduced SrTiO3 Ceramics Modified with La and Nb. Issue 9 (11th May 2013) - Teranishi, Takashi; Ishikawa, Yusuke; Hayashi, Hidetaka; Kishimoto, Akira; Katayama, Misaki; Inada, Yasuhiro; Zhou, X.‐D.
<x xml:space="preserve">Abstract</x> Ceramics of LaxSr1−xNbyTi1−yO3 (LSNT) were synthesized under various reducing atmospheres. Covering the specimens with graphite carbon felt under an Ar‐gas flow during sintering drastically enhanced the electrical conductivity, σ. Ti K‐edge absorption spectra indicated the presence of Ti3+ for heavily reduced specimens. The increase in conductivity was attributed to the 3d band of Ti3+. The maximum value for the figure of merit, ZT, was obtained for strontium titanate ceramics modified with both 5 mol% La and 5 mol% Nb, namely 5/5‐LSNT, exhibiting a ZT value of ~0.221 at 473 K. This high ZT value was almost 1.5 × larger than that of the conventional 10 mol% La‐doped sample, 10/0‐LSNT (ZT~0.144), and was mainly attributed to the larger Seebeck coefficient of the material.